Pengaruh Sarana Prasarana Serta Dukungan Sekolah Terhadap Pelaksanaan Kegiatan Ekstrakurikuler - Fahrid Maruf Alfiyana; Jenisa Tasya Kamila; Renata Nur Annisa; Yessi Vichaully (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
In an effort to develop the potential, interests and talents of students, the education organizers organize extracurricular activities which contain activity units that can channel the potential, interests and talents of students and can be developed optimally. Extracurricular activities have several supporting aspects so that they can be carried out well and effectively, such as the existence of adequate facilities and infrastructure as well as school support for the implementation of these activities. The aim of this research is to describe the influence of facilities and infrastructure as well as school support on the implementation of extracurricular activities at school. The research method used in this research is a qualitative research method, with the respondents being Extracurricular Guidance teachers. The data collection techniques used by researchers are observation, document and interview techniques. In analyzing the data, researchers used triangulation techniques, namely data reduction, data presentation and drawing conclusions.